Prepectoral Implant-Based Breast Reconstruction. Issue 9 (September 2017) - Highton, Lyndsey; Johnson, Richard; Kirwan, Cliona; Murphy, John
Abstract : Background: The development of acellular dermal matrices (ADMs) has facilitated single-stage implant breast reconstruction (IBR) following skin-sparing mastectomy. The conventional approach of postpectoral implant placement with lower pole ADM confers a good cosmetic result by improving lower pole projection and control, while minimizing issues of implant visibility, palpability, and rippling. This is balanced with potential disadvantages including pain, disruption of pectoral muscle function, and animation. We report the results of a prospective study of prepectoral IBR with total ADM coverage. Methods: Prepectoral IBR with total ADM coverage was performed in 106 patients (166 breasts) in our institution from 2013 to 2017. The cohort included patients undergoing immediate IBR (113 breasts) and revision of existing submuscular IBR (53 breasts). Patient demographics, surgical complications, and outcomes from a prospective database were analyzed. Results: At a mean follow-up of 485 days, patient satisfaction and cosmetic outcomes have been good, with no significant capsular contractures or animation deformity. Minor complications including delayed healing, red breast, or seroma occurred in 14 breasts (8.4%). Major complications including necrosis and implant loss occurred in 5 breasts (3 patients), with a total explantation rate of 3%. No patients required more than an overnight stay in hospital, and there were no delays to adjuvant treatment in therapeutic cases. Conclusion: Prepectoral implant placement with ADM cover is emerging as an alternative approach for IBR. This method facilitates breast reconstruction with a good cosmetic outcome for patients who want a quick recovery without potential compromise of pectoral muscle function and associated problems.